Diversity, Abundance and Distribution of Birds in Guna Mountains Community Conservation Area, South Gondar, Ethiopia - Destaye, Yibeltal; Zelelew, Shimelis Aynalem; Ashagrie, Mezgebu (Journal of Agriculture and Environmental Sciences, 2022)
Ethiopian highlands are the center of endemism for fauna including birds. However, due to poor management practice, the habitats of animals have been encroached on from time to time. The main objective of this study was to assess the diversity, abundance and distribution of birds in the Guna Mountain Community Conservation Area. The study was conducted from August 2019 to April 2020, in wet and dry seasons. A stratified random sampling design was used to classify habitats based on vegetation type. The habitat types were: Erica moorland, Guassa grassland, and Rocky with lobelia. Point transects count method for Erica moorland, but line transects method for both Guassa grasslands and Rocky with lobelia habitats were employed. Data were collected in the morning (6:00-10:00 A.M.) and late afternoon (4:00-6:00 P.M.). A Chi-square test was used to test the distribution of birds among the three habitats and difference on the abundance of birds between wet and dry seasons. A total of 76 bird species that belong to 12 orders and 35 families were identified. Four species are endemic to Ethiopia, and nine were endemic both to Ethiopia and Eritrea. Five species were Inter African migrants, 18 highland biome species, and two Palearctic migrant bird species were identified. The Passeriformes were the most dominant order with 44 species and account for 58%, whereas Galliformes, Cuculiformes, Apodiformes and Strigiformes were the least represented orders that have only one species each. Relatively, high diversity of bird species was observed in the grassland habitat (HËˆ =3.67) but the lowest species diversity was observed in the Rocky with lobelia habitat (HËˆ=2.6). The highest evenness was recorded in the rocky with lobelia habitat (E = 0.88), whereas the lowest evenness was recorded in Erica moorland (E = 0.79). The species abundance of birds during the wet and dry seasons was significantly different (Ï‡2 = 904.541, DF =1, p<0.001). There were also significant differences in the distribution of birds among the three habitats (Ï‡2 = 3315.965, DF =75, p<0.001). Food availability, vegetation composition and breeding sites have affected the variety of birds’ abundance in different habitats. It has been seen that habitat size, foraging modes and floristic composition influenced the distribution of birds. Grassland and highland biome restricted birds may be affected as they do not have any alternative foraging or breeding sites if the Guna Mountains Conservation Area habitat fragmentation continues. The area supports a variety of avian species with high endemics and habitat specifics. Conservation of the area is vital for habitat restricted and endemic birds. Keywords: Afro-alpine, Bird species diversity, Endemic birds, Guna Community Conservation Area